Explicit versus implicit social cognition testing in autism spectrum disorder - Callenmark, B.; Kjellin, L.; Rönnqvist, L.; Bolte, Sven (2014)
Although autism spectrum disorder is defined by reciprocal social-communication impairments, several studies have found no evidence for altered social cognition test performance. This study examined explicit (i.e. prompted) and implicit (i.e. spontaneous) variants of social cognition testing in autism spectrum disorder. A sample of 19 adolescents with autism spectrum disorder and 19 carefully matched typically developing controls completed the Dewey Story Test. 'Explicit' (multiple-choice answering format) and 'implicit' (free interview) measures of social cognition were obtained. Autism spectrum disorder participants did not differ from controls regarding explicit social cognition performance. However, the autism spectrum disorder group performed more poorly than controls on implicit social cognition performance in terms of spontaneous perspective taking and social awareness. Findings suggest that social cognition alterations in autism spectrum disorder are primarily implicit in nature and that an apparent absence of social cognition difficulties on certain tests using rather explicit testing formats does not necessarily mean social cognition typicality in autism spectrum disorder.